Maximum Sustainable Yield for the Passur river fishery of Bangladesh by using Surplus-production model - Rouf, Muhammad Abdur; Md Shahriar, Sheik Istiak; Rahman, Md Hafizur; Hasan, Md Mehedi; Antu, Al Hasan; Siddiqui, Md Noman (Bangladesh Journal of Zoology, 2021)
Maximum sustainable yield (MSY), fishing effort (fmsy) and total allowable catch (TAC) of major fishery in the Passur River, Bangladesh were estimated using surplus production model (Schaefer and Fox model) with observation-error estimator based on four years (2011-2014) catch and effort data. Fox model was especially highlighted in this study; the estimated value of MSY was 4.61 kg with corresponding fmsy of 13.51 units (200m2SBN/day). Moreover, the mean value of MSY and TAC with 95% confidence interval in stochastic method was 4.53 kg and 4.08 kg respectively with the 13.22 units of fishing effort (fmsy). The overall results provide clear evidence that the fishery of the Passur River is being overexploited in the months from December to March. Sustainable exploitation of this stock can be assured through reducing present fishing effort. In addition, TAC might be incorporated along with several existing fisheries management measures to ensure the compensation of this stock towards long term sustainability. Bangladesh J. Zool. 48(2): 301-312, 2020